2013
DOI: 10.1038/nature11846
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent activation of striatal direct and indirect pathways during action initiation

Abstract: Summary The basal ganglia are subcortical nuclei that control voluntary actions, and are affected by a number of debilitating neurological disorders1–4. The prevailing model of basal ganglia function proposes that two orthogonal projection circuits originating from distinct populations of spiny projection neurons (SPNs) in the striatum5,6 - the so-called direct and indirect pathways - have opposing effects on movement: while activity of direct-pathway SPNs purportedly facilitates movement, activity of indirect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

92
953
10
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,095 publications
(1,097 citation statements)
references
References 34 publications
92
953
10
5
Order By: Relevance
“…other deep networks, and are thought to represent network firing bursts (24)(25)(26). Using simultaneous electrical recordings and GCaMP6s imaging from the same GAD65 LH -GCaMP6s cells in vitro, we confirmed that GCaMP6s linearly reports spike firing rate (Fig.…”
Section: Resultssupporting
confidence: 59%
“…other deep networks, and are thought to represent network firing bursts (24)(25)(26). Using simultaneous electrical recordings and GCaMP6s imaging from the same GAD65 LH -GCaMP6s cells in vitro, we confirmed that GCaMP6s linearly reports spike firing rate (Fig.…”
Section: Resultssupporting
confidence: 59%
“…This interpretation is congruous with the canonical view of the basal ganglia in the generation of motoric responses (Albin et al, 1989;DeLong, 1990), a theory that received recent validation using modern neuroscientific and computational techniques (Dreyer et al, 2010;Kravitz et al, 2012; but see Cui et al, 2013). According to this theory, high concentration surges in dopamine release activate striatal medium spiny neurons comprising the direct pathway to promote directed action sequences (eg, reinforcement-directed active lever response), whereas moderate dopamine concentrations activate striatal medium spiny neurons comprising the indirect pathway to inhibit directed action sequences, and possibly switch the motivational drive of the animal to seek out alternative options (Dreyer et al, 2010;Kravitz et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A velocity reference signal enters the basal ganglia circuit which then generates opponent configuration reference signals that are sent to the level below. One possible neural implementation is suggested by the anatomy: the excitatory input to the striatum activates both the striatonigral and striatopallidal pathways [61], and the intrinsic organization of these two pathways transforms the uniform excitation into a pair of signals, one increasing and the other decreasing from a common mode signal. And finally, a time integral can be produced in the basal ganglia transforming a given magnitude of velocity error into a rate of change in the reference signal for body configuration control.…”
Section: Discussionmentioning
confidence: 99%